STIFFNESS VARIATION OF PEELED VENEER FROM Acacia mangium, Acacia hybrid (A. mangium x A. auriculiformis) AND Eucalyptus urophylla - Hien Mai, Trinh; Redman, Adam; Tat Thang, Nguyen (Journal of Forestry Science and Technology, 2019)
In this study, three Vietnamese common plantation species Acacia mangium, Acacia hybrid (A. mangium x A. auriculiformis) and Eucalyptus urophylla in total nine sites (three sites per species) were selected. Each site had a different silvicultural or age regime including trees of the appropriate age/size class to meet the requirements for veneer production. The largest trees were used for peeling veneer with dimensions were 2.8 mm thick × 1.3 m (same as log length) × 0.95 m. Acoustic stiffness determination was performed on the 2.8 mm thick × 1.15 m (same as log length) × 15 cm strips after they were air-dried to approximately 15% MC. The mathematical processing of selected frequencies is made from the geometrical characteristics and the weight of the strips. Dynamic MOE of Acacia hybrid veneer increased steadily with the radius before stabilising to an approximate average value of 14,100 MPa; MOE stabilisation begins at a radial distance of approximately 85 mm from the pith indicating that the mature state of wood starts from this point. Dynamic MOE of Acacia mangium veneer increased steadily with radius with no apparent trend of stabilisation detected in the outer part of the logs; this indicates that the mature state is not yet reached. Similarly, for Eucalyptus urophylla, the MOE values indicates that the mature state had not yet been reached due to the appearance of no stabilisation trend. The most apparent observation was Eucalyptus urophylla superiority in terms of veneer MOE (maximum 15,200 MPa). Both acacia species have similar maximum veneer MOE values around 13,500 MPa. Acacia mangium was shown to have a relatively long or late transition from juvenile to mature wood compared with the other two species, thus producing a relatively higher proportion of low stiffness material. Characterising veneer stiffness with square of radius position is also discussed in the paper.